Microstructure and properties of VN/Ag composite films with various silver content. (March 2017) - Guo, Hongjian; Han, Minmin; Chen, Wenyuan; Lu, Cheng; Li, Bo; Wang, Wenzhen; Jia, Junhong
Abstract: The VN/Ag composite films with various silver content were prepared by PLD technique, and the microstructures, mechanical and tribological properties at elevated temperature to 900 °C of films were investigated, respectively. The results show that the films were composed of the fcc VN and Ag nano-crystalline grains. With the increase of silver content from 8.2 to 56.1 at.%, the grain size increased and the surface morphology deteriorated gradually, the hardness and elastic modulus of the films decreased from 18.6 GPa, 226.3 GPa–8.1 GPa, 126.6 GPa, respectively. Only appropriate silver addition could improve the lubricity of the VN/Ag films. The film with 16.6 at.% Ag were found to be optimized for lubrication from RT to 900 °C. At low temperatures, the lubricant property of the film relied on the metal silver heavily. At elevated temperatures, a series of Magnéli phase (vanadium oxides) and the layered structure silver vanadates (such as Ag3 VO4, AgVO3 ) formed by tribochemical reactions in the contact area played a critical role in improving lubrication properties. A synergy of the lubricating Ag at low temperatures and the new lubrication phases generated at high temperatures could be responsible to the excellent lubricity of the VN/Ag films in wide temperature range. Highlights: The VN/Ag films with various silver content were fabricated by PLD technique. The fcc-VN and fcc-Ag nano-crystalline grains coexisted in VN/Ag films. The incorporation of Ag into the VN matrix deteriorated the mechanical properties. The films with 16.6 at.% Ag were found to be optimized for lubrication in a wide temperature range.